EVALUASI PROGRAM RASKIN DI KELURAHAN MUKTIHARJO KIDUL KECAMATAN PEDURUNGAN KOTA SEMARANG - Wicaksono, Unggul; Subowo, Ari; Marom, Aufarul (Journal of Public Policy and Management Review, 2013)
Raskin program goal is to reduce the burden of Poor Households expenditure by fulfilling most basic food needs in rice while the goal of the program is to increase access Raskin food to poor families to meet basic needs in order to strengthen household food security and prevent further loss of energy and protein consumption.Expectations of the program is that poor people do not have a shortage of food, thus their welfare would be slightly guaranteed,turns in the implementation of this program would occur Raskin many problems, including the problem in terms of misses the point,not the right quantity, right quality is not, and is not appropriately priced. Apart from the administrative side also found a problem that delays the advent of depositing the proceeds of the purchase of rice to bulog.